Developing person-centred care in hospices through the voice and leadership of nursing: lessons from the United Kingdom - Haraldsdottir, Erna; Cooper, Marie; Richardson, Heather (Frontiers in Health Services, 2025)
IntroductionNursing leadership and the voice of nurses are crucial for developing person-centred care in hospices. Concerns have been raised that, as palliative care has evolved from its original vision and become more integrated into the mainstream healthcare system, it has increasingly become medicalised. This paper presents an emancipatory practice development programme aimed at enhancing the visibility and voice of nursing and nurse leadership to improve person-centred care in hospices across the United Kingdom.MethodsThe project was a 10-month collaborative education programme for nursing practice leaders in hospices throughout the United Kingdom, running from September 2023 to July 2024. A total of 24 clinical and practice development leaders from eight different hospices participated. The Kirkpatrick model for evaluating learning programmes was adapted to create a framework for assessing the programme's outcomes and impact. The evaluation process utilised Collaborative Critical Creative Inquiry.ResultsThe key findings from the evaluation indicate that the programme created conditions for the participants to gain transformative insights and understanding that positively impacted their practice through emancipatory practice development.DiscussionThe programme enabled leaders of person-centred care in hospices to rekindle their vision for palliative care practice. The participants became more aware of how care was constructed within their organisations and recognised the assumptions that were often taken for granted—assumptions that influenced daily care practices that sometimes leaned towards a traditional medical model. They acquired new skills and knowledge that empowered them to engage more intentionally in making changes to enhance person-centred care.Conclusion and implications for practiceHumanising healthcare is a global agenda, and within hospice care, nurses are at the heart of transforming care to be more person-centred. They are well-positioned to reclaim the core principles of palliative care, as developed by Cicely Saunders, and push back against the medical model that has overshadowed the development and integration of palliative care into current healthcare systems. Nurses are expert practitioners and leaders who hold positions of authority within their organisations. Yet, for many, their change-making potential is not realised. Innovative learning and development programmes are an essential part of humanising healthcare, and emancipatory practice development programmes can unlock nurses' potential to lead this transformation.